2014
DOI: 10.1371/journal.pone.0112564
|View full text |Cite
|
Sign up to set email alerts
|

CD137 Expression Is Induced by Epstein-Barr Virus Infection through LMP1 in T or NK Cells and Mediates Survival Promoting Signals

Abstract: To clarify the mechanism for development of Epstein-Barr virus (EBV)-positive T- or NK-cell neoplasms, we focused on the costimulatory receptor CD137. We detected high expression of CD137 gene and its protein on EBV-positive T- or NK-cell lines as compared with EBV-negative cell lines. EBV-positive cells from EBV-positive T- or NK-cell lymphoproliferative disorders (EBV-T/NK-LPDs) patients also had significantly higher CD137 gene expression than control cells from healthy donors. In the presence of IL-2, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
0
37
0
1
Order By: Relevance
“…We previously reported that EBV infection induced ectopic but endogenous CD40 expression n T and NK cells thereby promoting their survival in an autocrine manner via a CD40 ligand, CD154, which was initially expressed on the surface of EBV-T/NK cells [19, 30]. In addition, we reported that EBV infection induced CD137 expression on the surface of T cells, which subsequently mediated anti-apoptotic signals [20]. Because NF-κB can be activated downstream of CD40 and CD137 [31, 32], EBV-induced CD40 or CD137 expression may play a role in NF-κB activation in EBV-T/NK cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that EBV infection induced ectopic but endogenous CD40 expression n T and NK cells thereby promoting their survival in an autocrine manner via a CD40 ligand, CD154, which was initially expressed on the surface of EBV-T/NK cells [19, 30]. In addition, we reported that EBV infection induced CD137 expression on the surface of T cells, which subsequently mediated anti-apoptotic signals [20]. Because NF-κB can be activated downstream of CD40 and CD137 [31, 32], EBV-induced CD40 or CD137 expression may play a role in NF-κB activation in EBV-T/NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…MOLT4 or MOLT4-DL cells were infected with EBV as described previously [19, 20]. Briefly, spontaneously produced EBV was prepared from the culture medium of B95-8 cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A definitive histological diagnosis requires the identification of atypical hematopoietic cells on a background of inflammatory, necrotic, and degenerating cells . Furthermore, ENKTCL is strongly linked to EBV, suggesting an important oncogenic role of the virus . The exceedingly rare clinical presentation of this case warranted the combined use of both immunophenotyping and genomic profiling to arrive at an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 95%
“…[1,6] Furthermore, ENKTCL is strongly linked to EBV, suggesting an important oncogenic role of the virus. [13,14] The exceedingly rare clinical presentation of this case warranted the combined use of both immunophenotyping and genomic profiling to arrive at an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%